2016
DOI: 10.3389/fmicb.2016.01638
|View full text |Cite|
|
Sign up to set email alerts
|

Community Composition and Abundance of Bacterial, Archaeal and Nitrifying Populations in Savanna Soils on Contrasting Bedrock Material in Kruger National Park, South Africa

Abstract: Savannas cover at least 13% of the global terrestrial surface and are often nutrient limited, especially by nitrogen. To gain a better understanding of their microbial diversity and the microbial nitrogen cycling in savanna soils, soil samples were collected along a granitic and a basaltic catena in Kruger National Park (South Africa) to characterize their bacterial and archaeal composition and the genetic potential for nitrification. Although the basaltic soils were on average 5 times more nutrient rich than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 122 publications
(165 reference statements)
8
29
0
Order By: Relevance
“…6) showed that some bacterial phyla increased with increasing soil nutrient content, while others decreased. It is consistent with Rughöft et al (2016) who reported that nutrient availability also drives the bacterial community composition. Moreover, these results agree well with the copiotrophic hypothesis (Fierer et al 2007), which predicts that fast-growing copiotrophic soil bacteria such as Proteobacteria, Actinobacteria, and Bacteroidetes prefer nutrient-rich environments, while slowgrowing oligotrophs (e.g., Acidobacteria, Nitrospirae) would thrive in oligotrophic soils.…”
Section: The Acidic Condition and Low Exchangeable Nh4 + -N And Nosupporting
confidence: 92%
See 1 more Smart Citation
“…6) showed that some bacterial phyla increased with increasing soil nutrient content, while others decreased. It is consistent with Rughöft et al (2016) who reported that nutrient availability also drives the bacterial community composition. Moreover, these results agree well with the copiotrophic hypothesis (Fierer et al 2007), which predicts that fast-growing copiotrophic soil bacteria such as Proteobacteria, Actinobacteria, and Bacteroidetes prefer nutrient-rich environments, while slowgrowing oligotrophs (e.g., Acidobacteria, Nitrospirae) would thrive in oligotrophic soils.…”
Section: The Acidic Condition and Low Exchangeable Nh4 + -N And Nosupporting
confidence: 92%
“…In contrast, differences in sorgoleone levels between sorghum lines did not influence the abundance of AOB, although plant treatments contained less AOB than controls. It has been recognized that AOA outnumber AOB in many habitats (Rughöft et al 2016;Herrmann et al 2012) and can play a Fig. 6 Relative abundance of 16S rRNAV4 bacteria based on OTU reads at 1 and 2.3 months.…”
Section: Discussionmentioning
confidence: 99%
“…This family is mostly represented by uncultivable genera; its cultivable representatives are filamentous, aerobic and mesophilic [51]. Ktedonobacteraceae was previously found in young soils [20,52,53]; thus, we suggest that representatives of this family are important at initial successional stages.…”
Section: Discussionmentioning
confidence: 76%
“…Particularly, the relative abundance of the members of Planctomycetes, Chloroflexi, and Actinobacteria phyla significantly differed in sandy loam soil compared to silty clay and clay soils. These results could be linked to large variation in soil nutrient, moisture, and texture properties across soil types (Hermans et al, ; Kuramae et al, ; Rughöft et al, ).…”
Section: Discussionmentioning
confidence: 99%